An Energy Balanced Algorithm of PEGASIS Protocol in WSN - Chakravarty, Kangka; Barman, Utpal (International Journal of Computer Sciences and Engineering, 2025)
Energy efficiency is the important work for wireless sensor network. Every node has limited energy .So to design Routing protocol in WSN ones should take care of less energy consumption. Already many routing algorithm has developed which result is less energy consumption. In this paper we have discussed all well-known PEGASIS routing algorithms based on grid which always focus on low energy consumption. Each algorithm is described in detail with their pros and cons along with their design issue .